Pendidikan Nilai dalam Tradisi Takbiran Keliling: Studi Kebersamaan dan Toleransi Sosial di Desa Apoho: Penelitian - Dayun Riadi; Azmi Heru; Huda Fikri; ⁠Yera Sella; ⁠Irli Sili Seli; Elsi Nisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify and analyze the educational values contained in the tradition of takbiran keliling carried out by the people of Apoho Village, Enggano District, North Bengkulu Regency. This tradition is not only a religious expression before Eid al-Fitr, but is also full of social and cultural values that can strengthen social cohesion in the community. A descriptive qualitative approach with ethnographic methods was used in this study, with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. The results of the study show that takbiran keliling contains values of togetherness, social tolerance, and character education that are transmitted informally to the younger generation. These values are manifested in cross-age and religious cooperation, mutual cooperation, and the active involvement of children and adolescents in social activities. This tradition forms an inclusive and educational relational space, and is a means of preserving local culture that is adaptive to changing times. Thus, takbiran keliling in Apoho Village can be used as a model for the practice of local wisdom-based value education that is relevant to the spirit of the Merdeka Curriculum and national character education.